Extramammary Paget's disease: Updates in the workup and management - Reza Nabavizadeh; Khushali B. Vashi; Behnam Nabavizadeh; Vikram M. Narayan; Viraj A. Master (Asian Journal of Urology)
Objective: Extramammary Paget's disease (EMPD) is a rare cutaneous malignant disease. Due to its rarity, there is a paucity of data regarding best treatment strategy. EMPD primarily affects apocrine gland-bearing skin areas such as the vulva, scrotum, and penis. Our objective was to provide a present-day rationale for diagnosis, pathogenesis, and treatment of EMPD with a focus on recent progress in workup and management of the disease. Methods: Literature on EMPD until February 2022 was assessed through PubMed, MEDLINE databases, and Google scholar. A narrative review of the most relevant articles was provided. Results: EMPD usually presents with indolent growth while usually being diagnosed primarily as carcinoma in situ. The foundation of EMPD treatment centers around prompt and accurate diagnosis, wide local or Mohs micrographic surgical excision with proper management towards the margin status, and careful consideration for lymphadenectomy in patients with regionally positive disease. Conventional chemotherapies are alternative treatments modality for patients with distant metastases; however, they sometimes have suboptimal efficacy. At present, there is no agreement regarding adjuvant or systemic therapies, although recent studies have shown several insights into the molecular pathogenesis, tumor biology, and genomics of the development and advancement of EMPD, which may lead to novel and targeted treatment approaches for metastatic EMPD in the future. Conclusion: Patients with EMPD should seek care from physicians with expertise in disease management and patient counseling. These patients should be surveilled with close follow-up to evaluate them for disease recurrence or progression. Global collaborations with groups such as the Global Society for Rare Genitourinary Tumors, and especially patient support groups are crucial in designing clinical trials to help elucidate more robust data in this orphan disease.